Implementation of microsatellite instability testing for the assessment of solid tumors in clinical practice. (26th December 2022) - Nakayama, Izuma; Shinozaki, Eiji; Kawachi, Hiroshi; Sasaki, Takashi; Yunokawa, Mayu; Tomomatsu, Junichi; Yuasa, Takeshi; Kitazono, Satoru; Kobayashi, Kokoro; Hayakawa, Keiko; Ueki, Arisa; Takahashi, Shunji; et al.
Abstract: Background: In Japan, microsatellite instability (MSI) testing for solid tumors was introduced in clinical practice in December 2018. Although immune checkpoint inhibitors (ICIs) are established standards of care for patients with MSI‐high tumors, the status of implementing MSI testing in clinical practice remains unclear. Methods: We retrospectively reviewed the medical records of patients with solid tumors who underwent MSI testing between January 2019 and December 2020 at our institution. Results: In total, 1, 052 MSI tests were performed in 1, 047 patients. Regardless of specimen volume and condition, the MSI status was successfully determined in 1, 041 (99.0%) tests, encompassing 27 tumor types (microsatellite stable [MSS] or MSI‐low: n  = 991 [95.2%] and MSI‐high: n  = 50 [4.8%]). Patients whose specimens were fixed with 20% neutral buffered formalin (NBF) and who had specimens with prolonged storage (98.4% and 95.4%) showed lower success rates than those whose specimens were fixed with 10% NBF and who had specimens with nonprolonged storage (100.0% and 99.6%), respectively. The prolonged turnaround time (TAT) in MSI‐high cases (median TAT: 24 days) was a critical issue that directly resulted in treatment delay. Of the 50 patients with MSI‐high tumors, 24 (48.0%) received ICIs and 34 (68.0%) were referred to the Department of Clinical Genetic Oncology where 6 (12.0%) patients were diagnosed with Lynch syndrome. Conclusions: MSI testing was successfully performed for various types of tumors and specimens in clinical practice. Our study results identified certain issues associated with the clinical implementation of MSI testing, including optimal specimen selection, extended TAT in MSI‐high cases, and awareness of hereditary tumors. Abstract : More than 1000 real‐world experiences have refined the versatility and reliability of MSI testing. However, turnaround time can be influenced by sample quality and MSI status. Furthermore, awareness about the importance of hereditary tumors by clinicians is a necessary aspect of future growth in precision oncology.